Accessing online data for youth mental health research: meeting the ethical challenges - Perez Vallejos, Elvira; Koene, Ansgar; Carter, Christopher J.; Hunt, Daniel; Woodard, Christopher; Urquhart, Lachlan; Bergin, Aislinn; Statache, Ramona (Springer, 2017)
This article addresses the general ethical issues of accessing online personal data for research purposes. The authors discuss the practical aspects of online research with a specific case study that illustrates the ethical challenges encountered when accessing data from Kooth, an online youth web-counselling service. This paper firstly highlights the relevance of a process-based approach to ethics (Markham and Buchanan, 2012) when accessing highly sensitive data and then discusses the ethical considerations and potential challenges regarding the accessing of public data from Digital Mental Health (DMH) services. It presents solutions that aim to protect young DMH service users as well as the DMH providers and researchers mining such data. Special consideration is given to service users’ expectations of what their data might be used for, as well as their perceptions of whether the data they post is public, private or open. We provide recommendations for planning and designing online research in an ethical manner that includes vulnerable young people as research participants. We emphasise the distinction between public, private and open data, which is crucial to comprehend the ethical challenges in accessing DMH data. Among our key recommendations, we foreground the need to consider a collaborative approach with the DMH providers while respecting service users’ control over personal data, and we propose the implementation of digital solutions embedded within the platform for explicit opt-out/opt-in recruitment strategies and ‘read more’ options (Bergin and Harding, 2016).